Comparative Evaluation of Canal Transport and Centralization Between ProTaper Next and XP-endo Shaper Systems Using CBCT Analysis: An In Vitro Study - Hamed Karkehabadi; Abbas Shokri; Negar Banitalebi; Roshanak Abbasi (International Journal of Dentistry)
Conclusions: Both buccolingually and mesiodistally, PTN led to greater apical transport than XPS and also showed a lower centering ratio.